2019
DOI: 10.1172/jci98554
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-host disease propagation depends on increased intestinal epithelial tight junction permeability

Abstract: Graft-versus-host disease (GVHD) is a complication of hematopoietic stem cell transplantation (HSCT) that affects multiple organs. GVHD-associated intestinal damage can be separated into two distinct phases, initiation and propagation, which correspond to conditioning-induced damage and effector T cell activation and infiltration, respectively. Substantial evidence indicates that intestinal damage induced by pretransplant conditioning is a key driver of GVHD initiation. Here, we aimed to determine the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 70 publications
1
58
0
Order By: Relevance
“…Although there have not been reports of intestinal barrier restoration and consequent reductions of systemic inflammation in HIV-infected patients, recent data demonstrate that increased permeability of intestinal epithelial tight junctions is necessary for persistence (10). Several possible mechanisms drive epithelial barrier breakdown during SIV/HIV infection (5,6) for example, reports suggest that the pro-inflammatory cytokines interferon-gamma (IFN) and tumor necrosis factor-alpha (TNF) trigger the breakdown of tight junctions between GI tract epithelial cells (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Although there have not been reports of intestinal barrier restoration and consequent reductions of systemic inflammation in HIV-infected patients, recent data demonstrate that increased permeability of intestinal epithelial tight junctions is necessary for persistence (10). Several possible mechanisms drive epithelial barrier breakdown during SIV/HIV infection (5,6) for example, reports suggest that the pro-inflammatory cytokines interferon-gamma (IFN) and tumor necrosis factor-alpha (TNF) trigger the breakdown of tight junctions between GI tract epithelial cells (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, three independent research groups decipher the molecular mechanism linking GVHD to changes in the species composition of the gut microbiota (Golob et al, 2019;Nalle et al, 2019;Stein-Thoeringer et al, 2019). The analysis of the gut microbiota of a cohort of patients with allo-HCT revealed an increase in Enterococcus faecium, a lactose auxotroph bacteria (which requires lactose for its in vitro growth), in the patient's gut microbiota along with inflammation and intestine damages (Stein-Thoeringer et al, 2019).…”
Section: Impact Of the Gut Microbiota On Gvhdmentioning
confidence: 99%
“…faecium may possibly mediate the pro-inflammatory process (Zitvogel and Kroemer, 2019). Although patients with GVHD have increased intestinal permeability, the distribution of zonula occludens-1 (ZO-1) and actin were found unaltered and, in most cases, epithelial damages are limited to apoptosis of crypt epithelial cells associated with an over-expression of myosin light chain kinase 210 (MLCK210) and increased myosin II regulatory light chain phosphorylation (Nalle et al, 2019). Non-muscle myosin II (NMII), notably NMIIA, a key Rho kinase target, plays a role in epithelial cell-cell adhesion by controlling the local E-cadherin accumulation at the cell-cell contact (Priya et al, 2015).…”
Section: Impact Of the Gut Microbiota On Gvhdmentioning
confidence: 99%
“…Occurring after chemotherapy conditioning and HSCT, GVHD may develop as a serious complication when donor immune cells recognize the recipient as foreign and attack healthy cells in host's tissues. GVHD mostly occurs in the gut through the disruption of epithelial tight junctions, destruction of epithelial cells and inflammation in association with dysbiosis (5)(6)(7)(8). A large multicenter study showed that gut microbiota composition independently predicted mortality in 1,362 HSCT patients with GVHD (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Given the association between microbiota composition and clinical outcome in both GVHD and HIV infection (5)(6)(7)(8)(9)(10)(11), strategies to modify the gut microbiota have come to light through dietary interventions, the antidiabetic drug metformin, selective antibiotics, probiotics, prebiotics, and fecal microbiota transplantation (FMT) (5,23,24). FMT refers to the transfer of fecal microorganisms from healthy donors into the GI tract of patients.…”
Section: Introductionmentioning
confidence: 99%